Mengevaluasi Perasaan Penerjemah: Analisis Appraisal terhadap Terjemahan Tindak Tutur Ekspresif dalam Novel Pulang - Risky, Ayu; Firmonasari, Aprillia (Jurnal Bahasa dan Sastra, 2024)
The study illuminates the complexities inherent in translating expressive language by analyzing the Indonesian novel Pulang by Leila S. Chudori and its English translation Home novel. Utilizing Appraisal discourse analysis, a robust linguistic framework for evaluating language, the study identify the translator's rendering of 155 expressive utterances from the source text into 158 corresponding passages in the English translation. The findings reveal salient patterns of alteration between the source and target texts. Specifically, shifts emerged in the translator's lexical choices pertaining to attitude, engagement, and graduation. While preserving the core ideas, the translated version exhibits distinct preferences for certain attitude markers, more frequent intensification, and a tendency to explicate engagement meanings more than the original Indonesian. Such modifications seem subtle yet prove consequential. The research indicates that altering the lexical or phrasal selections surrounding expressive speech can inadvertently distort the intended message and tenor, potentially diminishing the reader's investment and engagement with the literary work. Moving forward, translators seeking to produce more authentic translations of expressive texts must remain acutely cognizant of the cultural nuances ingrained in the source language and exercise care in choosing lexical items that accurately convey the original meanings and affect. Meticulous word choice preserves the vital expressive essence between languages. Overall, Appraisal discourse analysis demonstrates a robust framework for evaluating and enhancing literary translation quality.